2011
DOI: 10.1002/biot.201100010
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2‐mediated induction of phase 2 detoxifying enzymes by glyceollins derived from soybean exposed to Aspergillus sojae

Abstract: Numerous antioxidants have been reported to cause transcriptional activation of several antioxidant enzymes through binding antioxidant-response element on their promoter region. We, therefore, attempted to examine whether glyceollins, which share common structural features with many phase 2 enzyme inducers and antioxidant activity, could induce detoxifying/antioxidant enzymes. Glyceollins induced NAD(P)H:quinone oxidoreductase activity in a dose-dependent manner in both mouse hepatoma Hepa1c1c7 and its mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 38 publications
1
38
1
Order By: Relevance
“…These tumour inhibitory effects corresponded with significantly lower E2-induced progesterone receptor expression in the tumours, suggesting that the glyceollin mixture may be functioning as selective ER modulators, selectively antagonising ER function in a tissue type-specific manner (14,15) . In contrast to these reports, our data consistently suggested the oestrogenic activity of glyceollins, as shown in the E-screen assay and in the enhanced proliferation of MCF-7 cells carrying ER, and the increased expression of pS2, a typical biomarker for oestrogenic activity (11) . Therefore, we speculate that like isoflavones, glyceollins appear to exert both oestrogen-like and anti-oestrogenic activities depending on the physiological condition.…”
Section: Anti-cancer and Oestrogen-modulating Activitiescontrasting
confidence: 61%
See 1 more Smart Citation
“…These tumour inhibitory effects corresponded with significantly lower E2-induced progesterone receptor expression in the tumours, suggesting that the glyceollin mixture may be functioning as selective ER modulators, selectively antagonising ER function in a tissue type-specific manner (14,15) . In contrast to these reports, our data consistently suggested the oestrogenic activity of glyceollins, as shown in the E-screen assay and in the enhanced proliferation of MCF-7 cells carrying ER, and the increased expression of pS2, a typical biomarker for oestrogenic activity (11) . Therefore, we speculate that like isoflavones, glyceollins appear to exert both oestrogen-like and anti-oestrogenic activities depending on the physiological condition.…”
Section: Anti-cancer and Oestrogen-modulating Activitiescontrasting
confidence: 61%
“…Our recent study indicated that glyceollins have the potential to induce antioxidant enzymes and phase 2 detoxifying enzymes through the Nrf2-Kelch-like enoyl-CoA hydratase-associated protein 1 (Keap1) pathway (11) , although the mechanism of action how the compounds activate the Nrf2 signalling pathway needs to be defined (Fig. 3).…”
Section: Antioxidant Enzyme Inductionmentioning
confidence: 99%
“…heme oxygenase I (HO-1). Both glyceollin and genistein could enhance the Nrf2/HO-1 signaling pathway 31,32 . Upregulation of HO-1 could increase expression of Foxp3, a transcription factor for Treg, increasing the number and suppressive function of Treg 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The same study also showed Glys inhibition of H2O2-induced ROS production in hepatoma cells (hepa1c1c7) (Kim et al 2010b). Subsequent studies indicated that Glys antioxidant activity in hepatoma cells was through the upregulation of antioxidant enzymes (heme oxygenase 1, gamma-glutamylcysteine synthase, and glutathione reductase), by the induction of the nuclear translocation of nuclear factor eythroidderived 2-like 2 (Nrf2), a transcription factor and regulator of cellular antioxidant enzymes (Kim et al 2011b). Moreover, the study suggested that Gly caused the Nrf2-mediated enzyme induction through activation of thePI3K signaling pathway and by regulating Nrf2 interaction with kelch-like ECH-associated protein 1 (Keap1), which is an inhibitor of Nrf2 function (Kim et al 2011b).…”
Section: Glys Antioxidant Propertiesmentioning
confidence: 99%
“…Subsequent studies indicated that Glys antioxidant activity in hepatoma cells was through the upregulation of antioxidant enzymes (heme oxygenase 1, gamma-glutamylcysteine synthase, and glutathione reductase), by the induction of the nuclear translocation of nuclear factor eythroidderived 2-like 2 (Nrf2), a transcription factor and regulator of cellular antioxidant enzymes (Kim et al 2011b). Moreover, the study suggested that Gly caused the Nrf2-mediated enzyme induction through activation of thePI3K signaling pathway and by regulating Nrf2 interaction with kelch-like ECH-associated protein 1 (Keap1), which is an inhibitor of Nrf2 function (Kim et al 2011b). More recently, a study indicated that soybeans infected with Aspergillus oryzae had a high accumulation of Gly I and phytoalexin coumestrol, which significantly prevented H2O2-induced ROS production and lipid peroxidation in human HepG2 hepatoma cells (Jeon et al 2012).…”
Section: Glys Antioxidant Propertiesmentioning
confidence: 99%